New Active Cooling System to Prevent an Overheating on the Vehicle Disc Brake - Joni Dewanto; Oegik Soegihardjo; Agustinus N. Rolando Wijaya (Institute of Research and Community Outreach - Petra Christian University, 2018)
The brake is a major and vital component to slow down and stop a vehicle. If the brake malfunctions, it can cause a fatal accident or seriously injure either passenger or other road users. That is one reason why research is conducted to improve the capability and reliability of vehicle braking systems. The thermo-mechanical properties of the material for better disc brake components have been investigated. Some geometrics of the disc brake design models have also been studied to determine the heat distribution that occurs during braking. However, brake failure cases still occur frequently. Most of the brake failures are preceded by the occurrence of overheating when the vehicle is braked continuously on a declining road. This indicates that the heat dissipation system during braking does not work well. This study focuses on designing an unconventional brake system, that uses an active cooling system. Under conditions of large braking loads, the brake system will actively cool down by spraying water on the caliper so the brakes will not experience overheating. The design of this system consists of temperature sensors mounted on the caliper, an over-temperature control unit and also a cooling unit. The design is implemented on a four-wheel vehicle brake model. The increase of caliper temperature at the time of braking is simulated by putting the temperature sensor on the Bunsen burner. The results of this study shows that at various levels of temperature increases the system works very well.